أهمية المعنى في الترجمة عبر اطروحة بول ريكور - حيدر, السعيد (Maalim, 2026)
The aim of this study is to confront two concepts proposed respectively by both the meaning and the form. Within a comparative perspective, the analysis will focus on what Paul Ricoeur(1976) call " The Utterance Meaning " , on the one hand, and " The Utterer’s Meaning", on the other hand. Our aim is to underline the scientificity of meaning in favor of task of the translator.